Indicator species and co-occurrence pattern of sediment bacterial community in relation to alkaline copper mine drainage contamination - Qiusheng Yuan (Elsevier, 2021)
Contamination of alkaline copper mine drainage (AlkCuMD) causes serious damages to riverine ecosystem. Sediment bacterial community, as the fundamental component of biogeochemical processes, has been applied as an effective ecological indicator for various pollutants, but little is known about its relation to AlkCuMD. In this study, the composition variation, indicator species, and co-occurrence pattern of sediment bacterial community were studied in the Jinsha River, a typical AlkCuMD polluted large river in southwestern China. Results showed that significant sulfur (TSmax, 84.06 g/kg) and copper (Cumax, 1.63 g/kg) contamination from AlkCuMD decreased the richness and diversity of bacterial community, and the composition of bacterial community was significantly altered by copper, zinc, chromium, and total organic carbon. Moreover, the indicator species identified in the polluted sediments, including Thiovirga and Symbiobacterium, exhibited the functional traits of sulfur oxidation and metal(loid) cycling; while the indicator species in the unpolluted sediments were mainly associated with the nitrogen and phosphorus biotransformation. In addition, the bacterial co-occurrence pattern showed higher positive interactions and network connectivity at polluted sites, suggesting the potential enhancement of bacterial interspecific mutualistic relationships against AlkCuMD contamination. Therefore, this study provides an important evaluation of AlkCuMD influence on sediment bacterial community, and proposes the potential ecological indicators for evaluating AlkCuMD pollution in river sediments.